Phylogenetic relationships of Yucatan hairless pig with Asian and European breeds by mitochondrial DNA D-loop - Lemus , Clemente; Lemus, Gilberto; Bugarín, Job; Alonso , Rogelio; Ulloa, Raúl; Segura , José; Ayala , Miguel; Sansor , Raúl (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
In Mexico native pig genotypes exist whose populations face serious threats to survival. One of them is the Yucatan hairless pig (YUCMEX), for which limited information is available regarding its current conservation status. This study aimed to determine the phylogenetic relationship of YUCMEX with Iberian, wild pigs (WB), European, Asian, and commercial pigs using the mtDNA D-loop region. A total of 31 YUCMEX sequences and 77 mitochondrial haplotypes from GenBank were analyzed, aligned to reference sequence AJ002189. The study fragment, trimmed between positions 15435 and 15977, resulted in 543 base pairs. Genetic distances were calculated to compare YUCMEX with the other pig groups. Phylogenetic trees were constructed using the Neighbor-Joining method with Kimura’s two-parameter distance and 1000 bootstrap replicates. Additionally, a principal component analysis (PCA) was performed based on evolutionary distances. Among the 108 sequences analyzed, 41 variable sites and 44 haplotypes were identified. YUCMEX individuals grouped into four haplogroups (HA, HB, HC, HD), showing lower D-loop diversity and genetic distance from the Duroc breed. European and Asian haplotypes formed seven phylogenetic groups, clearly separating both regions. The YUCMEX haplogroups clustered into three lineages close to WB from Portugal and Spain but were distinct from Asian pigs and Eastern European WB haplotypes. These findings confirm the European—specifically Iberian—origin of the Yucatan hairless pig.